Key for identification of rock-forming minerals in thin section - Barker, Andrew J. (London CRC Press, 2014)
"The key for identification of rock-forming minerals provides an efficient and systematic approach to identifying minerals in thin-section. It is structured in the form of a dichotomous key, comparable to those widely used in botany and entomology. The present key gives a unique solution for each mineral. The key covers more than 150 of the most commonly encountered rock-forming minerals, plus a few rarer but noteworthy minerals, indicative of particular conditions. Illustrated in full colour, with high quality photomicrographs of each mineral, it also provides the most comprehensive atlas of rock-forming minerals currently available."--
1. Introduction -- 2. Key to rock-forming minerals in thin-section.
Includes bibliographical references and index.
Keywords: Rock-forming minerals; NATURE / Ecology; SCIENCE / Earth Sciences / Geology; TECHNOLOGY & ENGINEERING / Civil / Soil & Rock